Effect of Heat Input on Distortions and Residual Stresses Induced by Gas Tungsten Arc Welding in SS 316L to INCONEL625 Multipass Dissimilar Welded Joints - Harinadh Vemanaboina; B Sridhar Babu; Edison Gundabattini; Paolo Ferro; Kaushik Kumar (Advances in Materials Science and Engineering)
In the present study, distortion and residual stresses in the multipass welded joint were analyzed with respect to heat input. The welded joint was produced using the gas tungsten arc welding (GTAW) process with dissimilar Ni-based filler of ERNiCrMo-3. This dissimilar joint is essential in power generating nuclear and thermal plants operating at elevated temperatures. The distortion and residual stress measurements were taken using the Vernier height gauge and XRD method. To evaluate the mechanical properties, tensile testing was carried out at room temperature. The welded joint qualified the tensile test with an average value of 593 MPa. In the weld metal, a significant variation of residual stresses is measured on the top surface of the weldment along with the thickness with peak magnitude of 145 MPa to 180 MPa at the fusion zone.